2020
DOI: 10.7150/ijms.46234
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 promotes cell metastasis via inducing Angiogenesis and Epithelial Mesenchymal Transition in Esophageal Squamous Cell Carcinoma

Abstract: Non-muscle myosin heavy chain 9 (MYH9) is one novel low frequency mutated gene identified in esophageal squamous cell carcinoma (ESCC) using next-generation sequencing. However, its clinical relevance, potential function and mechanisms remain elusive. Methods: Genomic sequencing datas from 104 esophageal squamous cell carcinoma (ESCC) cases were screened a series of low frequency mutant genes. MYH9 was selected to further analyze its clinical significance, function and PCR-array was performed to explore its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In the initial study, MYH9 was reported as a tumor suppressor participating in the pathogenesis of squamous cell carcinoma 14 , 15 . However, some reversed studies showed that MYH9 functions as a potential oncogene in most tumors and promotes the tumor occurrence, metastasis and tumor stemness formation 16 - 19 , including esophageal squamous cell carcinoma and nasopharyngeal carcinoma 20 , 21 . These studies show the complexity and importance of MYH9 in tumor pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial study, MYH9 was reported as a tumor suppressor participating in the pathogenesis of squamous cell carcinoma 14 , 15 . However, some reversed studies showed that MYH9 functions as a potential oncogene in most tumors and promotes the tumor occurrence, metastasis and tumor stemness formation 16 - 19 , including esophageal squamous cell carcinoma and nasopharyngeal carcinoma 20 , 21 . These studies show the complexity and importance of MYH9 in tumor pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MYH9 is a widespread cytoplasmic myosin and is involved in the translocation of the skeleton proteins ( 54 ). Moreover, some studies showed that MYH9 was upregulated in gastric cancer, which could promote the transcription of β-catenin ( 55 ) and could be upregulated in esophageal squamous cell carcinoma (ESCC) facilitating cell metastasis ( 56 ). Also, MYH9 could bind with and degrade GSK3β through ubiquitin, therefore β-catenin was downregulated to induce the epithelial-mesenchymal transition in hepatocellular carcinoma ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-muscle myosin heavy chain9(MYH9) is widely expressed in various tissues and cells. MYH9 is abnormally highly expressed in esophageal squamous cell carcinoma 17 , breast cancer 18 , epithelial ovarian cancer 19 and acute myeloid leukemia 20 and is associated with poor prognosis. Researchers report that MYH9 degrades GSK3β protein through TRAF6-induced ubiquitination, enhancing the stem cell characteristics, migration, invasion, growth and sorafenib resistance of HCC cells 21 .…”
Section: Discussionmentioning
confidence: 99%